35 Review on endothelial cell loss of corneal transplants and possible correlations. (16th November 2022) - Franz, Ursula; Hennerbichler-Lugscheider, Simone; Bamschoria, Katharina
Abstract : The Tissue Bank of the Upper Austrian Red Cross in Linz, Austria, is a multi-tissue bank, processing corneal transplants (for PKP, for DMEK, pre-cut DMEK), homografts (aortic valve, pulmonary valve, pulmonal patch), amnion grafts (frozen or cryopreserved), autologous tissues and cells (ovarian tissue, cranial bone, PBSC) as well as investigational medicinal products and ATMPs (Aposec, APN401). This presentation sums up retrospective data of the endothelial cell count of corneae at the time of first evaluation and at the time of reevaluation before transplantation as well as the cell count of pre-cut DMEK before transplantation. Regarding corneal grafts it is advisable to review the data of the previous years to find potential factors influencing the cell count of corneal tissue. Certain factors as donor age or duration of time between death of the donor until the cornea is cultivated might have an impact on endothelial cell loss. 719 corneal transplants were included in this data comparison (PKPs, Corneae for DMEK and pre-cut DMEK), which were evaluated between January 2017 and March 2021. The average donor age was 66 years (22 to 88yrs). The average time until enucleation was 18 hours after death (3 to 44h). The mean duration of cultivating the cornea until reevaluation before transplantation was 15 days (7 to 29d). The average cell count at time of first evaluation was 2723 c/mm² (1550 to 3950c/mm²), at the time of reevaluation before transplantation 2613c/mm² (1650 to 3325c/mm²) and of the pre-cut DMEK transplants 2550c/mm² (2000 to 3233c/mm²). The results show an average cell loss of 6% from time of first evaluation compared to the time of reevaluation before transplantation and an average cell loss of 9% for pre-cut DMEK in comparison to the cell count at first evaluation. Dividing the donors in age groups of 10 years shows no noticeable difference in the results as the cell count at first evaluation compared to reevaluation shows cell loss between 4, 9% and 8, 8% with no tendency of increasing cell loss regarding donor age. The same seems to be the case regarding duration of cultivation until reevaluation. The aim of the data review was to determine the cell loss of corneal transplants and attempt to identify possible factors having an impact on endothelial cell loss of cultivated corneae. In conclusion the data comparison shows that donor age and time of cultivation seem to have no impact on cell loss.